Responsiveness to Sugar Solutions in the Moth Agrotis ipsilon: Parameters Affecting Proboscis Extension - Hostachy, Camille; Couzi, Philippe; Hanafi-Portier, Melissa; Portemer, Guillaume; Halleguen, Alexandre; Murmu, Meena; Deisig, Nina; Dacher, Matthieu (Frontiers in Physiology, 2019)
Adult moths need energy and nutrients for reproducing, and obtain them mainly by consuming flower nectar (a solution of sugars and other compounds). Gustatory perception gives them information on the plants they feed on. Feeding and food perception are integrated in the proboscis extension response, which occurs when their antennae touch a sugar solution. We took advantage of this reflex to explore moth sugar responsiveness depending on different parameters (i.e. sex, age, satiety, site of presentation, composition of the solution). We observed that starvation but not age induced higher response rates to sucrose. Presentation of sucrose solutions in a randomized order confirmed that repeated sugar stimulations did not affect the response rate; however, animals were sometimes sensitized to water, indicating sucrose presentation might induce non-associative plasticity. Leg stimulation was much less efficient than antennal stimulation to elicit a response. Quinine prevented and terminated sucrose-elicited proboscis extension. Males but not females responded slightly more to sucrose than to fructose. Animals of either sex rarely reacted to glucose but curiously, mixtures in which half sucrose or fructose were replaced by glucose elicited the same response rate than sucrose or fructose alone. Fructose synergized the response when mixed with sucrose in male but not female moths. This is consistent with the fact that nectars consumed by moths in nature are mixtures of these three sugars, which suggests an adaptation to nectar perception.